2019
DOI: 10.1021/acsami.9b13321
|View full text |Cite
|
Sign up to set email alerts
|

Nanoplasmonic 1D Diamond UV Photodetectors with High Performance

Abstract: Diamond nanowires have recently drawn substantial attention because of their unique physical and chemical properties for electrochemical sensors, optoelectronics, and nanophotonics applications. However, diamond nanowire-based ultraviolet photodetectors have not been reported because of the challenges involved in synthesizing crystalline diamond nanowires with controllable morphologies and, more fundamentally, the material's high carrier concentration with low mobilities that limits the obtainable photorespons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 48 publications
1
30
0
Order By: Relevance
“…With the tremendous development in UNCD synthesis and UNCD NW fabrication, many UNCD NWs based sensor applications have been explored, including N-UNCD NW based methane (CH4) gas sensors [73,74], B-UNCD NW based carbon monoxide (CO) gas sensor and sensor arrays [31,75], UV sensors based on UNCD NWs functionalized with platinum nanoparticles (NPs) [76], and piezoresistive B-UNCD NWs. The availability of this special type DNWs inspires research efforts to make use of both the unique physicochemical properties and geometrical advantages for applications in electrochemical sensors, biosensors, optoelectronics, and nanophotonics.…”
Section: Uncd Nw Sensor Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the tremendous development in UNCD synthesis and UNCD NW fabrication, many UNCD NWs based sensor applications have been explored, including N-UNCD NW based methane (CH4) gas sensors [73,74], B-UNCD NW based carbon monoxide (CO) gas sensor and sensor arrays [31,75], UV sensors based on UNCD NWs functionalized with platinum nanoparticles (NPs) [76], and piezoresistive B-UNCD NWs. The availability of this special type DNWs inspires research efforts to make use of both the unique physicochemical properties and geometrical advantages for applications in electrochemical sensors, biosensors, optoelectronics, and nanophotonics.…”
Section: Uncd Nw Sensor Applicationsmentioning
confidence: 99%
“…(a) Time-dependent photocurrent from the external and internal electrodes at 0 V bias when illuminated by 350 nm light at 0.01, 0.03 and 1 mW/cm 2 , and (b) PD spectral responsivity from external electrodes at 0 V bias when exposed to different wavelengths of 1 mW/cm 2 intensity. Reprinted with permission from[76]; © 2019, ACS.…”
mentioning
confidence: 99%
“…[303] In the case of diamond, although it is well-known as the hardest, the most thermally conductive, and the highest in breakdown voltage material among WBG semiconductors, the implementation of diamond nanowires in UV photodetectors is extremely rare. [311] This is because the synthesis of diamond nanowires in a reproducible way is still a challenging task due to the lack of a detailed understanding of the growth mechanism. [312] Recently, several approaches based on chemical vapor deposition and reactive-ion etching techniques have been employed to synthesis diamond nanowires, thus offering a promising pathway toward diamondbased UV sensors.…”
Section: Ultraviolet Sensorsmentioning
confidence: 99%
“…2 × 10 4 3.2 × 10 7 <0.026 [ 227] GaN/AlN NWs 300 -5.2 × 10 −14 2 × 10 3 -- [ 232] GaN NWs/Pt 380 --6.39 × 10 4 2.24 × 10 7 1.1 [ 228] GaN NWs/graphene 357 1.28 × 10 −4 -2 5 -- [ 303] AlN/GaN/AlN NWs 325 10 −9 -10 −12 -200-700 -- [ 310] GaN/AlN NWs 280-330 0.5 × 10 −9 -3.4 × 10 −9 -3 . 1 × 10 6 -12 × 10 6 -- [ 233] Diamond NWs 300 3 × 10 −6 7 × 10 −8 338 -0.02 [ 311] due to a variation of surface carrier given by ΔG = Δn s × e × × d 2 /L. Therefore, the sensitivity of sensors can be defined as ΔG/G = Δn s /n 0 .…”
Section: Gas and Humidity Sensorsmentioning
confidence: 99%
“…It has been found that the doping content and doping element, in general, significantly affect UNCD properties. For example, boron-doped UNCD is an excellent active material for deep UV photo-detectors, [15] whereas nitrogen-doped UNCD is a good material for gas sensing device but poor response to deep UV radiation. The present work focuses on the UNCD gas sensing device.…”
Section: Electrical Propertiesmentioning
confidence: 99%